2016
DOI: 10.1093/mnrasl/slw112
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of hard phase lags in the pulsed emission of GRO J1744−28

Abstract: We report on the discovery and energy dependence of hard phase lags in the 2.14 Hz pulsed profiles of GRO J1744-28. We used data from XMM-Newton and NuSTAR. We were able to well constrain the lag spectrum with respect to the softest (0.3-2.3 keV) band: the delay shows increasing lag values reaching a maximum delay of ∼ 12 ms, between 6 and 6.4 keV. After this maximum, the value of the hard lag drops to ∼ 7 ms, followed by a recovery to a plateau at ∼ 9 ms for energies above 8 keV. N uST AR data confirm this tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In the timing analysis, we find that the pulsed fraction is positively correlated to both the energy band (at 3-30 keV) and luminosity. This result is well in agreement with the reports by D' Aì et al (2015); Doroshenko et al (2015); Younes et al (2015);D'Aì et al (2016); Cui (1997). In addition, thanks to the stable pulse profiles in different energy bands, we studied the energy-dependent lags with respect to the 16-20 keV band.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the timing analysis, we find that the pulsed fraction is positively correlated to both the energy band (at 3-30 keV) and luminosity. This result is well in agreement with the reports by D' Aì et al (2015); Doroshenko et al (2015); Younes et al (2015);D'Aì et al (2016); Cui (1997). In addition, thanks to the stable pulse profiles in different energy bands, we studied the energy-dependent lags with respect to the 16-20 keV band.…”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that the hard X-ray lag is due to the Compton reverberation-like process (Lightman et al 1978;Payne 1980;Guilbert et al 1982;D'Aì et al 2016). In a nutshell, in a hot, thermal plasma hard X-rays can be produced by repeated Compton scattering, because the energy of the incident photons can be amplified by a factor of ∼ 1+ 4kT mec 2 for non-relativistic electrons per scattering, where the kT is the temperature of the hot plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation